Концентрація власності корпорацій та рівень розвитку фондового ринку - Rudenok, Olha; Laktionova, Oleksandra; Orlov, Vasyl (Dr. Viktor Koval, 2021)
Introduction. The ownership structure affects the stock market liquidity. In turn, stock markets are a key lever to ensure the efficient functioning and development of the country's economy as a whole. Recently, the widespread use of securities market instruments has become of paramount importance due to the limited opportunities for self-financing of enterprises and the shortage of external sources of financing. The performance of the stock market of its functions is largely determined by its characteristics, the implementation of which leads to positive structural changes in the economy. Aim and tasks. The main purpose of the article is to determine the correlation between the ownership concentration of corporations and the level of stock market development in Ukraine and the world. Results. The comprehensive characteristics of financial systems are characterized by the measurement of four categories for one of the key components of the financial sector, namely financial markets. Such categories include the depth of the financial market, the level of use of financial markets among individuals, the efficiency of financial markets in the provision of financial services, and the volatility of financial markets. A general description of the development of financial markets is given, it is determined that developing financial systems tend to be less deep as well as somewhat less efficient, their access and stability are on par with those of developed countries. The article shows the results of correlation-regression analysis between ownership concentration and the above categories, taking into account data from different countries. Conclusions. To determine the depth of financial markets, the article used the capitalization of the stock market as a percentage of GDP. Increasing the level of concentration of ownership leads to a decrease in this indicator. The inverse relationship between ownership concentration and characteristics of access to financial services has been confirmed. To analyze the efficiency of financial markets, this paper uses the ratio of the total value of traded shares to the average value of market capitalization for the analyzed period. The inverse relationship between ownership concentration and characteristics of efficiency has been also confirmed. Stability has a particularly low correlation with the other three characteristics. As a result, the direct relationship between ownership concentration and characteristics of financial markets stability has been confirmed.